2001
DOI: 10.1007/s00268-001-0033-4
|View full text |Cite
|
Sign up to set email alerts
|

Primary aldosteronism: Are we diagnosing and operating on too few patients?

Abstract: Many cases of potentially curable primary aldosteronism are currently likely to be diagnosed as essential hypertension unless screening tests based on suppression of renin are carried out in all hypertensive patients. More than half of the patients with primary aldosteronism detected in this way have normal circulating potassium levels, so measurement of potassium is not enough to exclude primary aldosteronism. When primary aldosteronism is diagnosed, fewer than one-third of patients are suitable for surgery a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
41
0
2

Year Published

2003
2003
2014
2014

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(43 citation statements)
references
References 46 publications
0
41
0
2
Order By: Relevance
“…Adenomas/hyperplasias o1 cm could be possibly missed on CT scan and therefore, if suppression tests confirm the diagnosis of PH, adrenal venous sampling (AVS) is indicated. 8 Furthermore, the use of ARR as the screening test has important clinical implicationsF more patients would be diagnosed and possibly cured when surgically treated. However, the indications for the use of the ARR in all hypertensive patients still remain controversialFsome authors dispute the validity of such an application.…”
Section: Introductionmentioning
confidence: 99%
“…Adenomas/hyperplasias o1 cm could be possibly missed on CT scan and therefore, if suppression tests confirm the diagnosis of PH, adrenal venous sampling (AVS) is indicated. 8 Furthermore, the use of ARR as the screening test has important clinical implicationsF more patients would be diagnosed and possibly cured when surgically treated. However, the indications for the use of the ARR in all hypertensive patients still remain controversialFsome authors dispute the validity of such an application.…”
Section: Introductionmentioning
confidence: 99%
“…1,5 However, multiple studies have shown that the accuracy of adrenal CT in localizing the source of aldosterone excess is poor (approximately 50%) and that in patients with primary aldosteronism who wish to pursue the surgical option for hypertension management, AVS is a key step in distinguishing between unilateral and bilateral adrenal disease. 1,[5][6][7][8][9][10][11][12][13] Some centres and a recent clinical practice guideline recommend that AVS be performed in all patients who have the diagnosis of primary aldosteronism and who want to pursue surgical management. 1,13 A more practical approach is the selective use of AVS who want to pursue the surgical option in the management of their hypertension.…”
mentioning
confidence: 99%
“…1,[5][6][7][8][9][10][11][12][13] Some centres and a recent clinical practice guideline recommend that AVS be performed in all patients who have the diagnosis of primary aldosteronism and who want to pursue surgical management. 1,13 A more practical approach is the selective use of AVS who want to pursue the surgical option in the management of their hypertension. doxazosin, terazosin and prazosin).…”
mentioning
confidence: 99%
“…45 Instead, a detailed time-consuming evaluation is necessary, especially in all hypertensive patients, to rule out primary aldosteronism which may be the cause of hypertension in up to 15% of these patients. 43,44 In a normotensive patient with a serum potassium level greater than 3.9 nmol/L, no further hormonal evaluation is necessary. The screening for subclinical primary aldosteronism should include, in addition to serum potassium, the upright aldosterone level to plasma renin activity (PRA) ratio, since a single value of aldosterone may be normal.…”
Section: Screening or Subclinical Primary Aldosteronismmentioning
confidence: 99%